Uji Aktivitas Antibakteri Ekstrak Kloroform dan Ekstrak Etanol Biji Bidara Laut (Strychnos ligustrina Bl) Terhadap Staphylococcus aureus ATCC 25923 dan Salmonella thypi - Sumiati, Eti (Biogenesis: Jurnal Ilmiah Biologi, 2014)
A research has been conducted on the antibacterial activity of Strychnos ligustrina seeds against Staphylococcus aureus ATCC 25923 in vitro. Strychnos ligustrina seeds extracted using two solvents, namely chloroform (chloroform extract) and 70% ethanol (ethanol extract) and analysis of the chemical content of the extract by thin layer chromatography and paper chromatography. The results of this study are expected to provide data activity of Strychnos ligustrina seeds as antibacterial scientifically. In this study, the chloroform extract and ethanol extract of Strychnos ligustrina seeds obtained by the filtration method with Soxhlet apparatus. Antibacterial activity test of chloroform extract and ethanol extract 70% from Strychnos ligustrina seeds performed using liquid dilution method, the parameters used are the MIC (minimum inhibitory concentration) and MKC (minimum killing concentration). MIC is determined by turbidity or clarity of the test solution, while MKC determined by scraping the respective concentrations of the extract / test solution on blood agar medium. The results showed that the chloroform extract and ethanol extract of Bidara Laut seed has antibacterial activity against Staphylococcus aureus ATCC 25923 and Salmonella thypi. MIC of each test extracts (chloroform and ethanol 70%) could not be determined because both of the test extract produce turbid color, while the MIC of the second test extract was 3.62% b/v for Salmonella thypi, 8.75% for Staphylococcus aureus ATCC 25923 (Strychnos ligustrina seeds chloroform extract), 22.5% for Salmonella thypi and 15% for Staphylococcus aureus ATCC 25923 (Strychnos ligustrina seeds ethanol extract). Results of thin layer chromatography and paper chromatography showed that the chloroform extract seeds contain alkaloids and steroids / triterpenoids, whereas the 70% ethanol extract contains alkaloids, tannins and steroids/triterpenoids. Keywords: antibacterial, chloroform extract, ethanol 70% extract, Strychnos ligustrina seeds, Salmonella thypi, Staphylococcus aureus